Síntese, estrutura e propriedades de complexos de Cu(II) e Tl(I) com ligantes triazenos monocatenados - Bresolin, Leandro (2003)
In this work we synthesized and determinate the crystalline/ molecular structure of three Cu(II) complexes and one Tl(I) complex, all of them showing monocatenated triazenide ligands previously deprotonated. We present too the crystalline/ molecular of 1,3-bis(4-nitrophenyl)triazene. [...]